Time lag between functional and structural lymphatic changes after lymphadenectomy: Insights from ICG lymphography and lymphatic ultrasound - Hisako Hara; Mitsuko Hirai; Makoto Mihara; Takashi Hirayama; Yasuhisa Terao (PLoS ONE, 2026)
Postoperative lower limb lymphedema is a common complication following pelvic or para-aortic lymphadenectomy for gynecologic cancers. Early detection of lymphatic dysfunction is crucial, but the temporal relationship between functional and structural changes remains unclear. This prospective observational study aimed to compare indocyanine green (ICG) lymphography and lymphatic ultrasound findings at multiple time points in the early postoperative phase. We enrolled 23 patients (46 lower limbs) who underwent pelvic and/or para-aortic lymphadenectomy for gynecologic malignancies. Each patient underwent ICG lymphography and lymphatic ultrasound preoperatively and at 1, 3, and 9 months postoperatively. ICG patterns were categorized as linear, splash, or stardust, while lymphatic vessel dilation ≥0.3 mm was defined as abnormal on ultrasound. At least one abnormal ICG finding was observed in 52.2% of limbs, and abnormal ultrasound findings were present in 65.2%. Among limb-timepoints with abnormal ICG findings, lymphatic dilation on ultrasound was observed in 32.6% overall, increasing to 52.6% at 9 months postoperatively, indicating increasing concordance between functional and structural abnormalities over time. Splash patterns on ICG were often not accompanied by lymphatic dilation, whereas stardust patterns were more likely to coincide with structural changes, especially at 9 months. Skin thickness increased significantly in the medial and lateral lower leg regions in limbs with stardust patterns. Our findings demonstrate a temporal dissociation between functional abnormalities detected by ICG and structural changes detected by ultrasound, suggesting that ICG lymphography may be more sensitive in the early phase. The combined use of both modalities may help capture the continuum from early functional disturbance to later structural remodeling and inform the optimal timing of intervention.